Efektivitas Metode Hibrida Ozonasi dan Adsorpsi Fly ash dalam Menurunkan Parameter Pencemar Organik Kompleks pada Air Lindi - Ayu Aprilia; Syafriadi Syafriadi; Nova Eliza fitri; Vitri Agustin; Riska Hasanatun Jannah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
Human activities, from household to industrial operations, generate liquid waste that poses a threat to the environment. Before discharge, liquid waste should be treated to ensure it is safe for release into the environment. This study aims to evaluate the effectiveness of a hybrid ozonation-adsorption method with varying contact times. This study collected leachate samples from the Rajabasa Landfill and used fly ash from the Tarahan Coal-Fired Power Plant as the adsorbent. First, the study used contact times of 20, 40, 60, and 80 minutes for ozonation. Subsequently, the 80-minute sample proceeded to the adsorption stage and was ultimately tested against six parameters. The measured parameters included COD, TSS, TDS, turbidity, UV254, and DO. The results showed that the 80-minute ozonation process significantly reduced TSS, TDS, and DO levels. However, the ozonation process still left intermediate compounds, which were subsequently removed by adsorption. Ultimately, the combination of the two processes yields good results, particularly for COD and UV254. This aligns with the theory that ozonation breaks down complex compounds while the adsorbent absorbs residual pollutants. This hybrid process achieves a 45.47% reduction in COD and an 87.83% reduction in UV254.